2016
DOI: 10.1182/blood-2016-02-697870
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of novel regulators of developmental hematopoiesis using Endoglin regulatory elements as molecular probes

Abstract: Key Points ENG regulatory elements target hemogenic mesoderm and hemogenic endothelium. Hemogenic progenitors can be enriched using these elements as molecular probes to discover novel regulators of hematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The existence of two haematogenic precursors that are broadly equivalent in their ability to produce haematopoietic lineages suggests that there are multiple cellular pathways to blood production in the yolk sac, one endothelial affiliated (haemangioblast) and one mesenchymal affiliated (haematomesoblast). The unequivocal role of transcriptional master regulators such as GATA1, GATA2, RUNX1, and TAL1 for in vivo blood cell emergence 8,19,21,32,33,[51][52][53][54][55][56][57][58][59][60][61][62][63] , and that E10.5 differentiated lineages cluster homogeneously, is consistent with the notion that haemangioblast and haematomesoblast differentiation routes must converge on the same molecular machinery to induce haematopoietic commitment. This likely occurs at the level of the E7.25-E7.75 Cdh5 + haemato-endothelial precursors, which might have the capacity for Haem group or endothelial lineage production but do not generally contribute to both outcomes.…”
Section: Discussionsupporting
confidence: 75%
“…The existence of two haematogenic precursors that are broadly equivalent in their ability to produce haematopoietic lineages suggests that there are multiple cellular pathways to blood production in the yolk sac, one endothelial affiliated (haemangioblast) and one mesenchymal affiliated (haematomesoblast). The unequivocal role of transcriptional master regulators such as GATA1, GATA2, RUNX1, and TAL1 for in vivo blood cell emergence 8,19,21,32,33,[51][52][53][54][55][56][57][58][59][60][61][62][63] , and that E10.5 differentiated lineages cluster homogeneously, is consistent with the notion that haemangioblast and haematomesoblast differentiation routes must converge on the same molecular machinery to induce haematopoietic commitment. This likely occurs at the level of the E7.25-E7.75 Cdh5 + haemato-endothelial precursors, which might have the capacity for Haem group or endothelial lineage production but do not generally contribute to both outcomes.…”
Section: Discussionsupporting
confidence: 75%
“…This cell population was also found to express hematoendothelial markers Cdh5, Icam2, Cd40, confirming the bipotent nature of these cells (45)(46)(47). As a high expression of the arterial-specific marker Delta-like, 4 (Dll4) is essential for the segregation of the endothelial lineage from the hematopoietic lineage (48,49), we looked at the Dll4 expression in this subset, and found that this cluster expresses a high level of Dll4.…”
Section: Loss Of Gata Factors Disrupts Hematopoietic-endothelial Cellmentioning
confidence: 60%
“…Interpretation of the phenotype of Tie2-Cre; Lrp2 flx/flx mice is confounded by the activity of the driver line in endothelial cells of all tissues, endocardial cells, and the hematopoietic cell line. Lrp2 is expressed in endocardial cells, myeloid cells, in developing endothelial cells, and is involved in hematopoiesis [ 43 , 44 , 45 ], suggesting that the phenotype of Tie2-Cre; Lrp2 flx/flx mice may be due to effects generated outside of the BBB.…”
Section: Discussionmentioning
confidence: 99%